(untitled) (Journal of Economic Research & Business Administration, 2018)
The course of industrial and innovative development of Kazakhstan, laid in the beginning of 2000, strategically correctly identified the main risks and priority directions for the development of the economy of Kazakhstan: a non-alternative course was chosen to diversify, increase the competitiveness of the economy through innovation and avoid dependence on raw materials. As analysis of innovative development in the Republic of Kazakhstan shows, innovative activity in the country plays a large role, but so far it is not the main factor of increasing the country’s competitiveness in the world market. In the conditions of building an innovation system, an economy based on knowledge, the only true development strategy is the intensification of innovation potential. The country’s innovation potential lies in the formation and formation of an educated nation, the compilation and integration of various types of sources, such as material, financial, intellectual and other. The most important factor in the growth of the innovation economy is the country’s intellectual potential. This article examines the issues of state regulation of innovation activities, including the features of the formation of an effective mechanism for financing innovation and the development of intellectual capital. Constant and continuous creation and implementation of innovations is the main factor of prosperity in the competitive struggle of any enterprise, region and country as a whole. The purpose of the research: to study the influence of the role of the state on the country’s innovative development; analysis of various applied complex and multilevel approaches on the part of the state to manage innovation activities; Identification of the most effective tools and mechanisms stimulating innovation activity. Research methods: general scientific (synthesis, deduction, induction, generalization, testing, survey, observation, forecasting, scientific abstraction, statistical analysis, logical), as well as methods of grouping and classification, expert evaluation. Results: the increasing role of the state as the most important regulator and stimulator of positive activity and social responsibility of private innovation business is defined. Creation of a favorable innovation climate is becoming the most important direction of state regulation in the innovation sphere, and such instruments as regulatory legal acts and economic incentives that contribute to improving the quality of innovations, reducing the costs of their implementation and increasing the socio-economic returns from innovations create conditions for the mass distribution of various innovative forms in the country. Scientific novelty: it is revealed that in order to strengthen the competitive positions of innovative business, the state should promote the formation and development of public and private partnerships in innovation activities. Also, the creation of an entire system, where the spheres of application of intellectual, creative work of people: science, education, culture should be put at the forefront, can also be an increase in innovative activity.